The fate of plastic leg rings used on geese and swans - Rees, Eileen C; Owen, M; Gitay, H; Warren, S (Wildfowl, 1990)
Engraved plastic leg rings have been placed on Barnacle Geese, Bewick's Swans and Whooper Swans to facilitate long-term studies of individual birds within the different populations. The rate of wear for Barnacle Goose rings was 0.23 mg/year which, on average, was less than 1% of the initial weight of the ring. The mean rate of ring loss was just 0.35% per annum for Barnacle Geese, but different groups of swans broke or lost their rings at rates varying from 5.8% for female Bewick's Swans to 27.6% for male Whooper Swans with Vynalast rings during the first two years after ringing. In some cases, the type of material used to make the swan rings affected their lifespan; Vynalast rings proved less durable than Darvic rings on Whooper Swans but there was no significant difference in the rate of ring loss for Darvic and Vynalast rings on Bewick's Swans. Whooper Swans proved more likely to break or lose their leg rings than Bewick's Swans, irrespective of the material used to make the rings. The mean minimum lifespan recorded for rings fitted to Bewick's Swans was significantly shorter for males than females but there was no difference between the sexes regarding the lifespan of Whooper Swan rings. Some individuals (predominantly male) were more likely to break or lose their rings than others. Different factors thought likely to influence the rate of ring loss included the diameter of the ring (larger rings had a lower survival rate), and the size and strength of the birds.